Life cycle impact and cost analysis of quarry materials for land-based enhanced weathering in Northern California - Hanna M Breunig; Patricia Fox; Jeremy Domen; Kumar, Ram; Ricardo Jorge Eloy Alves; Zhalnina, Kateryna; Anne Voigtländer; Deng, Hang; Arora, Bhavna; Nico, Peter (Journal of Cleaner Production, 2024)
Enhanced weathering (EW) is a CO2 removal (CDR) and sequestration strategy that accelerates the natural reactions of minerals that can store carbon from the atmosphere and biotic reactions. One method of EW is to apply finely ground silicate rocks to agricultural lands. EW has been demonstrated in laboratory and field tests, but great uncertainty remains regarding the life-cycle of using locally available rocks on candidate soils. We evaluate the life-cycle impacts, job creation, and cost of scenarios where fines and rocks mined from quarries in Oregon and Northern California are transported by truck and tilled into agricultural soils. Candidate quarry dust samples were classified as dacite, andesite, and olivine-bearing rocks, with EW potentials ranging from 125 to 760 kg CO2/metric tonne rock. We determined the olivine-bearing rock from Southern Oregon could achieve a levelized cost of CDR under the DOE Earthshot target of $100/t CO2, as long as application rates are 25 t/ha or more. Even andesite and dacite materials reach lower costs than commercial direct air capture technologies, with reduction in fines purchase and transport costs critical for achieving the Earthshot target. The results suggest that low-cost EW can be achieved using natural quarry materials, with average removal up to 2.2 t CO2e per hectare per year.